Second primary malignancies after ovarian cancer: A SEER-based analysis (1975-2016) - Zihui Yang; Xinyu Liu; Xi Yang; Qin-Ping Liao (Elsevier, 2022)
Objective: To investigate the risk of occurrence of second primary malignancies (SPMs) in survivors of ovarian cancer (OC) using large data from the Surveillance, Epidemiology, and End Results (SEER) database. Materials and methods: Multiple primaries standardized incidence ratios (MP-SIRs) to calculate the risk of developing second primary malignancies after a diagnosis of ovarian cancer. Results: Of our included 59,880 women with OC, 3972 cases (6.6%) developed 4495 s primary malignancies over an average follow-up period of 114.39 (±102.66) months. Overall, the risk of occurrence of second primary malignancies after a diagnosis of OC was greater than what would be expected for a reference US population (SIR = 1.05, 95%CI = 1.02-1.08, p-value < 0.05). The occurrence of second myeloid malignancies and second thyroid cancer were most notable across our latency periods. Among the most significant second primary malignancies by latency were malignancies of the appendix (SIR = 14.04, 95%CI = 5.65-28.93, p-value <0.05) at 2-11 months, the small intestine (SIR = 3.15, 95%CI = 1.76-5.2, p-value <0.05) at 12-59 months, and the urinary bladder (SIR = 1.63, 95%CI = 1.3-2.02, p-value <0.05) after 10 years of an OC diagnosis. Conclusion: Women with OC are at significant risk for the development of second primary malignancies across all sites, as compared to a reference US population, and may benefit from second primary malignancies site-specific screening post-diagnosis.